Russian as a foreign language in higher education: systematic approach to teaching vocabulary - Аnna A. Khokhlova; Natalya N. Nemich (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper is devoted to the peculiarities of vocabulary learning in the process of teaching Russian as a foreign language at a university. The main aspects, methods and techniques of working with lexical material depending on the stage of training are briefly highlighted. The purpose of the research is to substantiate the systemic systematic approach to teaching vocabulary. The research provides example materials and methods as well as teaching strategies for mastering vocabulary. The authors conclude that the research work points out the importance of systemic criteria in the process of mastering the grammatical and vocabulary material as well as the development of speech skills and abilities. The work contributes to the methodology of teaching of military and engineering students. The practical significance of the results of the study is due to the discussion and conclusion of the peculiarities of vocabulary learning in the process of teaching Russian as a foreign language in higher education.